2017
DOI: 10.1523/jneurosci.1525-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylsphingosine Promotes α-Synuclein Pathology in Mutant GBA-Associated Parkinson's Disease

Abstract: Glucocerebrosidase 1 () mutations responsible for Gaucher disease (GD) are the most common genetic risk factor for Parkinson's disease (PD). Although the genetic link between GD and PD is well established, the underlying molecular mechanism(s) are not well understood. We propose that glucosylsphingosine, a sphingolipid accumulating in GD, mediates PD pathology in -associated PD. We show that, whereas GD-related sphingolipids (glucosylceramide, glucosylsphingosine, sphingosine, sphingosine-1-phosphate) promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
195
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(206 citation statements)
references
References 61 publications
10
195
0
1
Order By: Relevance
“…This could be attributed to accumulation of the substrate, lysosomal glucosylceramide, which was shown to increase alpha‐synuclein aggregation . Recent work has also shown that glucosylsphingosine, which is more abundant in the cytoplasm, might also contribute to alpha‐synuclein aggregation . More recently, we found that mitochondrial oxidant stress and increased oxidation of dopamine resulted in direct modification of GCase that led to its decreased activity and ultimately lysosomal dysfunction .…”
Section: Glucocerebrosidase (Gba1)supporting
confidence: 55%
See 1 more Smart Citation
“…This could be attributed to accumulation of the substrate, lysosomal glucosylceramide, which was shown to increase alpha‐synuclein aggregation . Recent work has also shown that glucosylsphingosine, which is more abundant in the cytoplasm, might also contribute to alpha‐synuclein aggregation . More recently, we found that mitochondrial oxidant stress and increased oxidation of dopamine resulted in direct modification of GCase that led to its decreased activity and ultimately lysosomal dysfunction .…”
Section: Glucocerebrosidase (Gba1)supporting
confidence: 55%
“…GlcCer and glucosylsphingosine spill over into the cytoplasm, where they can be further metabolized by neutral GCase2 to ceramide and sphingosine, respectively. Accumulation of glucosylsphingosine and sphingosine also contributes to toxicity in GD …”
Section: Glucocerebrosidase (Gba1)mentioning
confidence: 99%
“…Moreover, a significant increase in α‐syn dimers has been observed on incubation with GlcCer‐containing liposomes . The effects of GlcCer could be secondary to that exerted by GlcSph, which triggers the formation of oligomeric α‐syn in young GD/PD mouse brains, thus potentially increasing PD risk in GD patients and carriers . Furthermore, it has been recently demonstrated that the reduction of ceramide species associated with GCase deficiency may contribute to the impaired secretion and intracellular accumulation of α‐syn …”
Section: Mechanisms Underlying the Cross Talk Between Gcase And α‐Synmentioning
confidence: 99%
“…Whereas reduced GBA activity is associated with GBA1 mutations, and has been reported in both sporadic PD and heterozygous GBA-PD patients, as well as in D409V/WT, L444P/WT, and N370S/WT heterozygous GBA mutant or heterozygous Gba knockout (WT/-) mouse brain [13,14], hemizygous Gba knbockout ( Gba WT/- ) mouse neurons and glia do not show mitochondrial defects [10]. It thus remains unclear whether and how heterozygous GBA mutations, particularly those commonly encountered in PD patients (L444P and N370S), contribute to mitochondrial dysfunction associated with PD.…”
Section: Introductionmentioning
confidence: 99%